The Research guide A primer for residents, other health care trainees, and practitioners - Harvey, Bart J.; Lang, Eddy S.; Frank, Jason R. (Ontario, Canada Royal College of Physicians and Surgeons of Canada, 2011)
A step-by-step guide for novice researchers and their supervisors. Written and reviewed by Canadian experts, this practical and accessible guide enables new and experienced researchers to effectively design a study, conduct the research and interpret the findings. Use as a stand-alone or modular curriculum.
STARTING: 1. A research road map: Fifteen steps to a successful research project (and ten pitfalls to avoid) -- 2. Research in residency, other health care training, and practice: Why, when and how? -- 3. Finding a research supervisor -- 4. Research teams and networks -- 5. Looking for an academic mentor.

PLANNING: 6. Conceiving and formulating the research question -- 7. Searching the literature -- 8. Data: Variables and levels of measurement.

DESIGNING: 9. Research methods and design: Bringing the research question to life -- 10. Developing and assessing health measurement items and scales -- 11. Surveys -- 12. Medical record review studies -- 13. Administrative database research -- 14. Health professions education research -- 15. Systematic reviews -- 16. An introduction to qualitative research.

PROPOSING: 17. Writing a research proposal -- 18. Getting to "approved": Concepts, guidelines and processes in ethics applications -- 19. Research funding and other resources.

CONDUCTING: 20. Sampling, recruiting and retaining study participants -- 21. Pilot studies -- 22. Data collection and data management -- 23. Managing and monitoring a study -- 24. Data analysis: Descriptive statistics -- 25. Data analysis: Hypothesis testing, sample size and study power.

REPORTING: 26. Interpreting your research findings -- 27. Writing effective abstracts -- 28. Communicating your research with slide and poster presentations -- 29. How to write a health science paper -- 30. Knowledge translation -- 31. Responsibility and integrity: Disseminating research findings to the public.

REFLECTING: 32. So, you've finished your first research project...now what?
Award 2012 Medical Book Awards Special Recognition: Physician Category
"Reprinted with an index February 2012"--Page facing title page.
Includes bibliographical references and index.
Keywords: Medicine -- Research; Health behavior -- Research -- Methodology; Primary health care -- Methodology; Exercise -- Health aspects -- Research -- Methodology